Analysis of the Clinical Efficacy of Dendritic Cell –cytokine Induced Killer Cell-based Adoptive Immunotherapy for Colorectal Cancer. (18th August 2021) - Xu, Huiru; Qin, Weishan; Feng, Huijing; Song, Dong; Yang, Xiaoling; Zhang, Junping
ABSTRACT: Background: To analyze the efficacy and safety of dendritic cell – cytokine – induced killer (DC-CIK) immunotherapy combined with chemotherapy for colorectal cancer. Method: A retrospective analysis was conducted in 116 patients from February 2012 to December 2017, who were divided into postoperative adjuvant chemotherapy group alone, combined DC-CIK immunotherapy group, advanced cancer palliative care group, and palliative care + DC-CIK immunotherapy group, to evaluate cellular immune function, disease-free survival(DFS) and overall survival(OS). Results: In the adjuvant therapy and palliative care group, the percentages of CD3+, CD8+ and NK cells after treatment were significantly lower than before, whereas in the other two groups given DC-CIK immunotherapy, the percentages of CD3+, CD8+, NK and NKT cells after treatment were all higher than before, with a significant increase compared with the chemotherapy group ( P < .05). DFS (42.4 ± 5.26 m) in the group receiving postoperative adjuvant chemotherapy + DC-CIK immunotherapy was significantly longer than that (23.5 ± 2.79 m) in the group only given postoperative adjuvant chemotherapy ( P < .05). OS in the group receiving palliative care + DC-CIK immunotherapy was slightly longer than that in the group only given palliative care for advanced cancer (29 m vs 26 m, P > .05).Conclusion: Combination with DC-CIK immunotherapy could effectively improve cellular immune function. Postoperative adjuvant chemotherapy in combination with DC-CIK immunotherapy could significantly prolong DFS, but palliative care in combination with DC-CIK immunotherapy did not significantly prolong OS in patients with advanced cancer.